Monumental tombs of the Hellenistic age : a study of selected tombs from the pre-classical to the early imperial era - Fedak, Janos, 1946- (Phoenix. Supplementary volume (Toronto, Ont.), 1990)
Most of the grandiose and often ostentatious Hellenistic monumental tombs were power- fully expressive and symbolic structures, built to glorify and display the wealth and power of kings, queens, nobles, and other persons of influence or to serve as shrines for the worship of the heroized dead. They were inventive in design and form, created to demonstrate the achievements of the dead in a public architecture of permanence and durability. This lavishly illustrated monograph brings together previously scattered information about Hellenistic funerary monuments and Janos Fedak's own research on the exterior architecture of these impressive structures in the Mediterranean region. The author first establishes a typology of main tomb forms and then considers some of the predecessors of the Hellenistic tombs. He explores the variations of form that resulted from differences in climate, building materials, and social and religious customs. Adherence to strong local traditional practice in building is visible in each region, but new ideas and novel funerary architecture were welcomed everywhere in the Hellenistic world. Fedak's wide-ranging approach makes the work of interest not only to specialists in Greek architecture and archaeologists but also to students of classical studies and historians of art and religion.